Identification of Pests and Diseases in Red Chili Plants (Capsicum Annuum L.) in Nangsri, Manisrenggo, Klaten - Eliuta Denisa Ekawati; Tri Wiharti; Anwari Adi Nugroho (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Red chilies are one of the important types of vegetables cultivated commercially in tropical countries. Insect pests are one of the obstacles in efforts to increase the production of red chili ornamental plants. There are some farmers who do not understand the types of pests that exist in red chili plantations. This research aims to identify the types of pests that attack red chili plants in Nangsri Manisrenggo Village and observe the symptoms of pest and disease attacks. The methods used are observation and interviews. The data obtained was analyzed descriptively qualitatively. The results of the research show that there are 2 types of disease, namely fungi that cause leaf spots, Pestalotia sp and Cercospora sp, and 6 types of pests that attack red chilies, namely: Thrips spp., peach aphids (Myzus persicae), armyworms (Spodoptera litura), flies fruit (Bactrocera spp.), mites (Tetranychus sp.; Polyphagotarsonemus sp.) and whitefly (Bemisia tabaci).